Analisis Prioritas Komoditas Unggulan Perkebunan Daerah Kabupaten Buru (Pre-eminent Commodity Preference Analysis of Plantation of Sub-Province Buru) - Hidayah, Ismatul (Badan Penerbitan Universitas Widyagama Malang, 2010)
As component of in development planning in level of Propinsi/kabupaten is required [by] region potency analysis either in aspect biofisik and also economic social included in of determination of pre-eminent commodity of area with approach LQ ( Location Quotient). Determination is important with consideration that availability and capability Resource ( nature, legal capital and man) to yield and markets all commodities which can be produced in a region in simultan relatively limited. Result of research indicates that there is 5 plantation commodity in sub-province Buru which included in bases sector mean the commodity in Â Maluku province has comparability excellence ( LQ > 1) that is cacao ( LQ = 5,80) , cashew ( LQ = 5,27), Clove ( LQ = 3,48), Nutmeg ( LQ = 1,87 ), and coffee ( LQ = 1,74). Â Key word : Pre-eminent commodity, Plantation, LQ (Location Quotient)